Środki zabezpieczające stosowane wobec przestępców wykazujących zaburzenia osobowości - Góralski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article discusses the criminal law and criminology issues of the precautionary measures used against criminals with personality disordersIt analyses the notion of human personality, personality disorders and their influence on the criminal responsibility of offenders. The discussion presented in the article refers to the relevant provisions of the Criminal Code of 1932, the Criminal Code of 1969 and the applicable provisions of the Criminal Code of 1997. The article also presents the measures used against criminals with personality disorders provided for in the Act of 22nd November 2013 on proceedings against persons with mental disorders posing athreat to life, health or sexual freedom of others. It also analyses the regulations of the amended Criminal Code as of 20th February 2015 concerning precautionary measures used against criminals with personality disorders such as electronic monitoring, therapy and addiction therapy.
Keywords: osobowość ludzka; środki ostrożności; przestępcy z zaburzeniami osobowości; psychopatia; dyssocjalne zaburzenia osobowości; antyspołeczne zaburzenia osobowości; monitoring elektroniczny; terapia; terapia uzależnień